2021
DOI: 10.21203/rs.3.rs-142984/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistence and baseline determinants of seropositivity and reinfection rates in health care workers up to 12.5 months after COVID-19

Abstract: We assessed the duration and baseline determinants of antibody responses to SARS-CoV-2 spike antigens and the occurrence of reinfections in a prospective cohort of 173 Spanish primary health care worker patients followed up initially for nine months and subsequently up to 12.5 months after COVID-19 symptoms onset. Seropositivity to SARS-CoV-2 spike and receptor binding domain antigens up to 149-270 days was 92.49% (90.17% IgG, 76.3% IgA, 60.69% IgM). In a subset of 64 health care workers who had not yet been v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…We showed that 35.8% of people infected almost a year ago and not vaccinated were no longer seropositive particularly if they were >60 years of age, were smokers, and had experienced an asymptomatic infection. Other studies have shown a similar [22] or lower (e.g., 4% in healthcare workers) [23] proportion of people with no longer detectable antibodies a year after infection. We have shown that infected people may benefit from vaccination given the significant increase in antibody levels after vaccination, in line with other reports [2,24,25].…”
Section: Discussionmentioning
confidence: 66%
“…We showed that 35.8% of people infected almost a year ago and not vaccinated were no longer seropositive particularly if they were >60 years of age, were smokers, and had experienced an asymptomatic infection. Other studies have shown a similar [22] or lower (e.g., 4% in healthcare workers) [23] proportion of people with no longer detectable antibodies a year after infection. We have shown that infected people may benefit from vaccination given the significant increase in antibody levels after vaccination, in line with other reports [2,24,25].…”
Section: Discussionmentioning
confidence: 66%
“…Of the 3282 papers initially retrieved, we included 91 cohort studies evaluating the onset of reinfection, severe and very severe/lethal COVID‐19 among 15,034,624 previously infected subjects (Figure 1), either among health care workers (27 publications; n = 37,598 2,8,9,15,17,24,36,38,42–59 ) or in the general population (67 publications; n = 14,997,026 3–7,10,12,16–23,25–27,43,49,60–106 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a total of 158,478 reinfections were recorded among the 15,034,624 subjects with a previous infection, 2–10,12,13,15–27,36,38,42–107 corresponding to a pooled rate of 0.97% (95% CI: 0.71%–1.27%—Table 1; Figure 2). The summary rate of reinfection rose to 1.07% (95% CI: 0.73%–1.46%) when only the 69 datasets with a more conservative time lag of ≥90 days between the two episodes were considered 3–6,8–10,12,18–23,25,26,36,42–44,46–50,52–56,59,61–65,67–69,72–84,86,87,89,91–96,98,101,103,105–107 and it slightly varied by reinfection definition criteria (0.93% vs 1.01% when considering studies with high vs low risk of misclassification). The risk of reinfection was higher among health care workers as compared to the general population (1.20% vs 0.90), and among females (0.79% vs 0.55% among males), although these estimates showed largely overlapping confidence intervals.…”
Section: Resultsmentioning
confidence: 99%
“…Only 14 (9.3%) of the study participants reported having associated comorbidities; thus, it was not possible to correlate the association of comorbid conditions with a decrease or increase in antibody response after vaccination. A study from Western India reported that there was no significant difference in the seroconversion with regard to any comorbid condition, except those with hypertension, where the seroconversion rate is low and the antibody level as well [ 13 ]. A high seroconversion rate (98%) among Sri Lankan HCWs with comorbid conditions such as diabetes, chronic kidney disease, or hypertension was reported [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Association of an increase of 10% COVID-19 vaccine coverage with a reduction of the average case fatality rate by 7.6% has been reported by researchers from Taiwan [ 12 ]. The longevity or persistence of protective antibodies produced after COVID-19 infection has been reported to be up to 6 months and beyond [ 13 , 14 ]. Thus, more research is needed to determine the presence and persistence of antibodies developed after COVID-19 vaccination and their protective role, which will finally determine the effectiveness of vaccination.…”
Section: Introductionmentioning
confidence: 99%